Penyuluhan Peraturan Hukum terkait Keselamatan dan Kesehatan Kerja (K3) bagi Pekerja Bangunan - Pangestika, Elza Qorina (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
Basically the housing construction process is an activity that contains many elements of danger. Occupational safety and health (K3) knowledge is important for construction workers to avoid work accidents caused by human and equipment negligence. The result of this community service activity is that after participating in socialization that has been carried out by the community, in this case the construction workers in the construction project for the Kailila Urban Houses housing development which is located at Jalan Kesejahteraan Sosial No.6 Ngestiharjo Village, Kasihan District, Bantul Regency, their knowledge has increased mainly regarding regulations law on occupational safety and health (K3). The implementation method in this community service activity uses the conversation method regarding occupational safety and health (K3).